Impact of the healthcare reorganization of the Local Health Authority services in Rieti (Italy) during the SARS-CoV-2 pandemic - De Luca, A.; Flammini, G.; Vittorini, P.; Muselli, M.; Mastrantonio, R.; Cipollone, C.; Gentile, M.; Petti, A.; D'Innocenzo, M.; Fabiani, L. (Annali di Igiene Medicina Preventiva e di Comunità, 2025)
Background. The need to contain the spread of the SARS-CoV-2 pandemic has forced national and local organizations to define and implement targeted emergency response and management measures. As the knowledge about the infection grew, a wider range of organizational measures were deployed. Methods. This study involves the SARS-CoV-2 infected people managed by the Local Health Authority of Rieti (Italy). Diagnostic test waiting times and hospital admission rates in the Province of Rieti are investigated as the pandemic evolved. Trends were analyzed in relation to the tempora spreading of SARS-CoV-2, to the organizational actions taken by the Local Health Authority of Rieti, and to the deployment of actions across the territory. A municipalities classification of the province of Rieti was conducted after a cluster analysis based on the diagnostic test waiting times and the hospital admission rates. Results. Our findings show a declining trend, thus indicating a possible positive effect of the measures taken to contain the pandemic. The cluster analysis of the municipalities of the Province of Rieti makes evident an inhomogeneous geographical distribution of examined parameters (diagnostic test waiting times and the hospital admission rates), demonstrating the capability of Local Health Authority of Rieti to reach even the most disadvantaged areas and implying that the differences are due to the demographical variabilities. Conclusion. Despite some limitations, this study outlines the importance of management measures in response of the pandemic. These measures should adapt to social, cultural and geographical nature of the territory involved. The findings of the present study will contribute to the update of further pandemic preparedness plans of the Local Health Authorities.